2019
DOI: 10.1002/nop2.235
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial self‐efficacy in adolescents with type 1 diabetes

Abstract: Aim To analyse psychosocial self‐efficacy in adolescents with type 1 diabetes, evaluate associations between self‐efficacy and metabolic control and background variables and determine psychometric properties of the Finnish Diabetes Empowerment Scale (Fin‐DES‐28). Design A descriptive correlational survey. Methods The data were collected with the Finnish Diabetes Empowerment Scale from 13–16‐year‐old adolescents with type 1 diabetes ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
1
7
3
Order By: Relevance
“…School district policies must provide the numbers of school nurses necessary to provide safe care (NASN, 2015b), which includes education and reinforcement of behaviors that lead to increased self-efficacy for T1D management in students of all ages, regardless of the length of diabetes duration. Numerous studies have failed to demonstrate gender differences in self-efficacy for T1D management (Chih et al, 2010;Survonen, Salanterä, Näntö-Salonen, Sigurdardottir, & Suhonen, 2019;Winsett et al, 2010), yet, in the current study, higher SEDM overall mean and scale item scores were associated with females. The mean age for boys and girls in this sample did not differ statistically, suggesting that age was not a factor.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…School district policies must provide the numbers of school nurses necessary to provide safe care (NASN, 2015b), which includes education and reinforcement of behaviors that lead to increased self-efficacy for T1D management in students of all ages, regardless of the length of diabetes duration. Numerous studies have failed to demonstrate gender differences in self-efficacy for T1D management (Chih et al, 2010;Survonen, Salanterä, Näntö-Salonen, Sigurdardottir, & Suhonen, 2019;Winsett et al, 2010), yet, in the current study, higher SEDM overall mean and scale item scores were associated with females. The mean age for boys and girls in this sample did not differ statistically, suggesting that age was not a factor.…”
Section: Discussioncontrasting
confidence: 54%
“…Numerous studies have failed to demonstrate gender differences in self-efficacy for T1D management (Chih et al, 2010; Survonen, Salanterä, Näntö-Salonen, Sigurdardottir, & Suhonen, 2019; Winsett et al, 2010), yet, in the current study, higher SEDM overall mean and scale item scores were associated with females. The mean age for boys and girls in this sample did not differ statistically, suggesting that age was not a factor.…”
Section: Discussioncontrasting
confidence: 53%
“…The current study finding showed that most of the studied adolescents did not attend any with Gutierrez-Colina etal., (2020) (43) who assessed 44 young adult with type 1 diabetes preparing to transition to adult care and found that young adults had lower selfefficacy at the baseline assessment. On the other hand, this finding is contradicted with Survonen etal., (2019) (44) who examined psychosocial self-efficacy in 189 adolescents with type 1 diabetes and stated that the adolescents self-efficacy level was good at the baseline assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Self‐efficacy is a psychological factor known to have an influence on management of the chronic disease (Survonen et al, 2019 ), cardiac rehabilitation and perceived health‐related QOL (Cuadrado et al, 2018 ). Defined by Bandura in the framework of the social learning theory of causation, self‐efficacy explains the influence of people's perception of their capabilities on their behaviour, motivation and emotional and cognitive patterns (O’Leary, 1985 ).…”
Section: Introductionmentioning
confidence: 99%